How to Selecting the Installation Intrauterine Devices [IUD] Placenta Post in East Java, Indonesia?: Regression Analysis - Zainiyah, Hamimatus; Anggraeni, Novi; Vidayati, Lelly Aprilia (International Journal of Psychosocial Rehabilitation, 2020)
Intrauterine Device [IUD] Post Placenta is an IUD that is placed within 10 minutes after the release of the placenta in labor. From observations made by researchers, it is found that the use of post placenta IUD in East Java General Hospital is still low, 15.2% of 221 mothers give birth in 2019. Aim of The Study is analyzing the determinants of postpartum Intrauterine Device [IUD] selection. Materials and Methods: A cross-sectional. The research variables were husband's support, mother's knowledge, culture, the role of health workers, and the selection of postpartum Intrauterine Device [IUD] installation with a population of 221 June 2019. Analysis by test logistic regression. Result: Research result Husband support variable with selection of postpartum Intrauterine Device [IUD] sig .006, OR 95%, EXP (B) 4,305, 95% CI, Lower 1,509, Upper 12,282, Postpartum maternal knowledge about postpartum Intrauterine Device [IUD] with the selection of Intrauterine Device [IUD] postpartum value sig .036, OR 95%, EXP (B) 5,934, CI 95%, Lower 1,126, Upper 31,262, Variable culture with the selection of Intrauterine Device [IUD] postpartum value sig .001, OR 95%, EXP (B) 25,320, CI 95%, Lower 3,660, Upper 175,152, Variable role of health workers by choosing Intrauterine Device [IUD] postpartum value sig .046, OR 95%, EXP (B) 3.082, CI 95 %, Lower 1,019, Upper 9,319. Conclusion: Culture provides the largest contribution in the selection of Intrauterine Device [IUD] in addition to husband's support, mother's knowledge, the role of health workers influences the selection of post placenta IUD contraception,